Novel Yersinia enterocolitica Prophages and a Comparative Analysis of Genomic Diversity - Liang, Junrong; Kou, Zengqiang; Qin, Shuai; Chen, Yuhuang; Li, Zhenpeng; Li, Chuchu; Duan, Ran; Hao, Huijing; Zha, Tao; Gu, Wenpeng; Huang, Yuanming; Xiao, Meng; et al. (Frontiers in Microbiology, 2019)
Yersinia enterocolitica is a major agent of foodborne diseases worldwide. Prophage plays an important role in the genetic evolution of the bacterial genome. Little is known about the genetic information about prophages in the genome of Y. enterocolitica, and no pathogenic Y. enterocolitica prophages have been described. In this study, we induced and described the genomes of six prophages from pathogenic Y. enterocolitica for the first time. Phylogenetic analysis based on whole genome sequencing revealed that these novel Yersinia phages are genetically distinct from the previously reported phages, showing considerable genetic diversity. Interestingly, the prophages induced from O:3 and O:9 Y. enterocolitica showed different genomic sequences and morphology but highly conserved among the same serotype strains, which classified into two diverse clusters. The three long-tailed Myoviridae prophages induced from serotype O:3 Y. enterocolitica were highly conserved, shared ≥ 99.99% identity and forming genotypic cluster A; the three Podoviridae prophages induced from the serotype O:9 strains formed cluster B, also shared more than 99.90% identity with one another. Cluster A was most closely related to O:5 non-pathogenic Y. enterocolitica prophage PY54 (61.72% identity). The genetic polymorphism of these two kinds of prophages and highly conserved among the same serotype strains, suggested a possible shared evolutionary past for these phages: originated from distinct ancestors and entered pathogenic Y. enterocolitica as extrachromosomal genetic components during evolution when facing selective pressure. These results are critically important for further our understanding of phage roles in host physiology and the pathology of disease.